Chemical and biological metal nanoparticles as antimycobacterial agents: a comparative study - Singh, Richa; Nawale, Laxman U.; Arkile, Manisha A.; Shedbalkar, Utkarsha U.; Wadhwani, Sweety A.; Sarkar, Dhiman; Chopade, Balu Ananda (International Journal of Antimicrobial Agents, 2015)
Resistance among mycobacteria leading to multidrug-resistant and extensively drug-resistant tuberculosis is a major threat. However, nanotechnology has provided new insights in drug delivery and medicine development. This is the first comparative report to determine the activity of chemically and biologically synthesised silver nanoparticles (AgNPs) and gold nanoparticles (AuNPs) against mycobacteria. Screening data revealed the high mycobactericidal efficiency of AgNPs, with minimum inhibitory concentrations (MICs) of <3 mu g/mL, whereas no such activity was exhibited by AuNPs at concentrations up to 100 mu g/mL. Moreover, in vitro and ex vivo THP-1 infection model assays showed greater efficacy of chemical AgNPs compared with biogenic AgNPs to inhibit active and dormant stage mycobacterial growth. Up to 40% cytotoxicity against human cell lines was observed at a AgNP concentration of 10 x MIC (30 mu g/mL) after 48 h. AgNPs were shown to have more specificity towards mycobacteria than towards other Gram-negative and Gram-positive pathogenic bacteria. The selectivity index was found to be in the range of 11-23, indicating the potential of these nanoparticles for use in developing new therapeutics for tuberculosis. (C) 2015 Elsevier B.V. and the International Society of Chemotherapy. All rights reserved.
Keywords: Antibiotic resistance; Antimycobacterial agent; Cytotoxicity; Mycobacteria; Nanoparticles; tuberculosis

Carboxymethyl cellulose-grafted mesoporous silica hybrid nanogels for enhanced cellular uptake and release of curcumin - Tiwari, Neha; Nawale, Laxman U.; Sarkar, Dhiman; Badiger, Manohar V. (Gels, 2017)
Mesoporous silica nanoparticles (MSNs) with ordered pore structure have beensynthesized and used as carriers for the anticancer drug curcumin. MSNs were functionalizedwith amine groups and further attached with carboxymethyl cellulose (CMC) using 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide (EDC) coupling chemistry, which increased the hydrophilicityand biocompatibility of MSNs. The functionalized MSNs (MSN-NH2and MSN-CMC) werecharacterized using Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM),Dynamic Light Scattering (DLS), N2adsorption, X-Ray Diffraction (XRD), Thermo GravimetricAnalysis (TGA) and Fourier Transform Infrared Spectroscopy (FT-IR). Thein vitrorelease of curcuminfrom the –NH2and CMC functionalized MSNs (MSN-cur-NH2and MSN-cur-CMC) was performedin 0.5% aqueous solution of sodium lauryl sulphate (SLS). The effect of CMC functionalization ofMSNs towards cellular uptake was studied in the human breast cancer cell line MDA-MB-231 andwas compared with that of MSN-NH2and free curcumin (cur). Both MSN-NH2and MSN-CMCshowed good biocompatibility with the breast cancer cell line. The MTT assay study revealedthat curcumin-loaded MSN-cur-CMC showed better uptake as compared to curcumin-loadedMSN-cur-NH2. Free curcumin was used as a control and was shown to have much less internalizationas compared to the curcumin-loaded functionalized MSNs due to poor bioavailability. Fluorescencemicroscopy was used to localize the ﬂuorescent drug curcumin inside the cells. The workdemonstrates that CMC-functionalized MSNs can be used as potential carriers for loading and releaseof hydrophobic drugs that otherwise cannot be used effectively in their free form for cancer therapy.

Click-chemistry-based multicomponent condensation approach for design and synthesis of spirochromene-tethered 1,2,3-triazoles as potential antitubercular agents - Chavan, Pramod V.; Pandit, Kapil S.; Desai, Uday V.; Wadgaonkar, Prakash P.; Nawale, Laxman; Bhansali, Sujit; Sarkar, Dhiman (Research on Chemical Intermediates, 2017)

Conformational studies of Ant-Pro motif-incorporated cyclic peptides: gramicidin S and avellanin - Kotmale, Amol S.; Sangtani, Ekta; Gonnade, Rajesh G.; Sarkar, Dhiman; Burade, Sachin; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (New Journal of Chemistry, 2018)
This paper reports conformational changes observed in cyclic bioactive peptides such as gramicidin S and avellanin upon incorporation of a pseudo-beta (C9) Ant-(D)Pro turn motif in their structural frameworks. Solution-state studies suggested that a synthetic gramicidin S analog exhibits a beta-sheet conformation with C9 and C17 intramolecular hydrogen bonding patterns, while its truncated analog disturbs the beta-sheet conformation. Structural details were obtained using a combination of CD studies, X-ray crystal structure studies and nOe-based MD simulation studies.

Click chemistry based multicomponent approach in the synthesis of spirochromenocarbazole tethered 1,2,3-triazoles as potential anticancer agents - Chavan, V, Pramod; Desai, V, Uday; Wadgaonkar, Prakash P.; Tapase, Savita R.; Kodam, Kisan M.; Choudhari, Amit; Sarkar, Dhiman (Bioorganic Chemistry, 2019)
A series of spirochromenocarbazole tethered 1,2,3-triazoles were synthesized via click chemistry based one-pot, five component reaction between N-propargyl isatins, malononitrile, 4-hydroxycarbazole, aralkyl halides and sodium azide using cellulose supported CuI nanoparticles (Cell-CuI NPs) as the heterogeneous catalyst. Antiproliferative activity of all the synthesized compounds was investigated against panel of cancer cell lines such as MCF-7, MDA-MB-231, HeLa, PANG-1, A-549, and THP-1. Many of the synthesized compounds exhibited good anti-proliferative activity against breast (MCF-7 and MDA-MB-231) and cervical (HeLa) cancer cells with IC50 values less than 10 mu M. In case of MCF-7 cells, among the nine compounds that showed good anti-proliferative activity, compounds 6f and 6j were found to be highly potent (IC50 , = 2.13 mu M and 4.80 mu M, respectively). In case of MDA-MB-231, three compounds (6k, 6j and 6s) showed antiproliferative activity amongst which 6k was the most potent one (IC50 = 3.78 mu M). On the other hand, in cervical cancer HeLa cells, compounds 6b, 6g, 6s and 6u showed excellent antiproliferative activity (IC50 = 4.05, 3.54, 3.83, 3.35 mu M, respectively). All the compounds were found to be nontoxic to the human umbilical vein endothelial cells (HUVECs). AO and EtBr staining and fluorescence microscopy studies of the active compounds (IC50 < 5 mu M) suggested that these compounds induce cell death by apoptosis.
Keywords: 1; 2; 3-Triazolylspirochromenocarbazole; Anticancer; Apoptotic assay; Click chemistry; Cytotoxicity; heterogeneous catalysis; Multicomponent synthesis

Conventional and microwave-assisted organic synthesis of novel antimycobacterial agents bearing furan and pyridine hybrids - Desai, Nisheeth C.; Bhatt, Kandarp; Jadeja, Dharmpalsinh J.; Mehta, Harsh K.; Khedkar, Vijay M.; Sarkar, Dhiman (Drug Development Research, 2022)
Drug resistance in tuberculosis poses a serious threat to humanity because currently available antitubercular drugs are ineffective against Mycobacterium tuberculosis (M. tuberculosis). As a result, the approval of Bedaquiline and Delamanid for the treatment of drug-resistant tuberculosis was accelerated. Still, there is an urgent need to search for new antitubercular drugs with novel mechanisms of action (MoA). Due to this, we have designed a synthetic strategy by utilizing microwave-assisted organic synthesis. We have compared our method with the conventional procedure, and the data show that our procedure is more effective in the preparation of title compounds. A unique series of 1-(2-(furan-2-yl)-5-(pyridin-4-yl)-1,3,4-oxadiazol-3(2H)-yl)-3-(aryl)-pr op-2-en-1-ones (5a-o) was synthesized utilizing conventional and microwave-assisted techniques. Synthetic compounds were investigated for antitubercular activity against Mycobacterium TB H37Ra and Mycobacterium bovis (M. bovis). Compound 5b was reported to be the most effective against M. tuberculosis H37Ra (97.69 percent inhibition at 30 mu g/ml) and M. bovis (97.09 percent inhibition at 30 mu g/ml). An in silico binding affinity study of mycobacterial enoyl-acyl carrier protein reductase (InhA) reveals the binding mechanism and thermodynamic interactions that determine these molecule's binding affinity. Compound 5b had a high glide score of -8.991 and low glide energy of -49.893 kcal/mol.
Keywords: Antitubercular activity; microwave-assisted organic synthesis; Molecular docking

Coumarin hybrids: dual-target candidates for future antimicrobial and antitubercular therapies - Bavishi, Abhay; Vala, Hardev; Thakrar, Shailesh; Swami, Sagar; Sarkar, Dhiman; Shukla, Rushit; Kamdar, Jignesh; Shah, Anamik (Future Medicinal Chemistry, 2025)
Aims: This study aimed to synthesize, characterize, and evaluate the antimicrobial and antitubercular activities of two novel series of coumarin-based derivatives (Series 5 and Series 9), focusing on their structure-activity relationship (SAR) and molecular docking interactions with key bacterial enzymes. Materials & methods: Series 5 (5a-5j) and Series 9 (9a-9t) compounds were synthesized and characterized using spectroscopic techniques. Their antimicrobial and antitubercular activities were evaluated against Mycobacterium tuberculosis, Staphylococcus aureus, Bacillus subtilis, and E. coli. IC50 values were determined, and molecular docking studies were conducted to assess binding interactions with M. tuberculosis enoyl-ACP reductase (InhA) and E. coli DNA gyrase B. Results: Series 5 compounds exhibited moderate activity, with 5f, 5 g, 5i, and 5j showing notable inhibition. Series 9 derivatives displayed superior dual-target inhibition, with 9t, 9c, 9a, 9b, and 9p achieving >90% inhibition against S. aureus and B. subtilis. The lowest IC50 against M. tuberculosis was observed for 9c (1.50 mu g/mL), followed by 9a (2.84 mu g/mL) and 9b (2.73 mu g/mL). Molecular docking confirmed strong binding interactions, correlating with observed biological activities. Conclusions: Series 9 compounds, particularly 9t, 9c, and 9a, demonstrate high potential as dual-target antimicrobial drug candidates. Further optimization may enhance their therapeutic efficacy. [GRAPHICS]
Keywords: Antimicrobial activity; antitubercular agents; Coumarin derivatives; Molecular docking studies; structure-activity relationship (SAR); thiophene-based compounds